Antibody-guided identification of Achromobacter xylosoxidans protein antigens in cystic fibrosis - Cecilia Sahl; Sounak Chowdhury; Johan Malmström; Lisa I. Påhlman (mSphere)
ABSTRACT Persistent bacterial airway infection is a hallmark feature of cystic fibrosis (CF). Achromobacter spp. are gram-negative rods that can cause persistent airway infection in people with CF (pwCF), but the knowledge of host immune responses to these bacteria is limited. The aim of this study was to investigate if patients develop antibodies against Achromobacter xylosoxidans, the most common Achromobacter species, and to identify the bacterial antigens that induce specific IgG responses. Seven serum samples from pwCF with Achromobacter infection were screened for antibodies against bacteria in an ELISA coated with A. xylosoxidans, A. insuavis, or Pseudomonas aeruginosa. Sera from pwCF with or without P. aeruginosa infection (n = 22 and 20, respectively) and healthy donors (n = 4) were included for comparison. Serum with high titers to A. xylosoxidans was selected for affinity purification of bacterial antigens using serum IgGs bound to protein G beads. The resulting IgG-antigen complexes were then analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Selected antigens of interest were produced in recombinant form and used in an ELISA to confirm the results. Four of the seven patients with Achromobacter infection had serum antibodies against Achromobacter. Using patient serum-IgG for affinity purification of A. xylosoxidans proteins, we identified eight antigens. Three of these, which were not targeted by anti-P. aeruginosa antibodies, were expressed recombinantly for further validation: dihydrolipoyl dehydrogenase (DLD), type I secretion C-terminal target domain-containing protein, and domain of uncharacterized function 336 (DUF336). While specific IgG against all three recombinant antigens was confirmed in the patient serum with high titers against Achromobacter, DLD and DUF336 showed the least binding to serum IgG from pwCF without Achromobacter spp. infection. Using serum IgG affinity purification in combination with LC-MS/MS and confirming the results using ELISA against recombinant proteins, we have identified bacterial antigens from A. xylosoxidans.IMPORTANCEAchromobacter species are opportunistic pathogens that can cause airway infections in people with cystic fibrosis. In this patient population, persistent Achromobacter infection is associated with low lung function, but the knowledge about bacterial interactions with the host is currently limited. In this study, we identify protein antigens that induce specific antibody responses in the host. The identified antigens may potentially be useful in serological assays, serving as a complement to culturing methods for the diagnosis and surveillance of Achromobacter infection.